Analisis Faktor yang berhubungan dengan Pencegahan Stunting pada Anak Usia 2-5 Tahun berdasarkan Teori Health Promotion Model (HPM) - Ribka Putri Sholecha; Esti Yunitasari; Ni Ketut Alit Armini; Yuni Sufyanti Arief (Universitas Airlangga, 2019)
Introduction: Indonesia still faced nutritional problems in children is like stunting. Stunting is one of conditions of malnutrition in child that need to be solved in Indonesia because it can affect the quality of the next generation. This study aimed to analyze the factors related to prevention of stunting in children based on Theory of the Health Promotion Model (HPM).Methods: This study used a cross-sectional design. The population was mothers who have children aged 2-5 years with number of samples are 141 people using purposive sampling technique. The independent variables were prior related behavior, education level, socio-economic status, perceived benefits to action and perceived barrier to action. Dependent variable was prevention of stunting. Data were collected using questionnaire and analyzed using logistic regression with a significance level α <0.05.Results: A positive stunting prevention behavior were 66.7% (94 people). Factors related to stunting prevention behavior were prior related behavior (p=0.03). While for other independent factors are level of education (p=0.74), socioeconomic status (p=0.07), perceived benefits to action (p=0.35) and perceived barrier to action (p=0.31) have no relationship with stunting prevention. The result of analysis on the prior related behavior had 2.81 times better in stunting prevention with a significance level is 0.03.Conclusion: The behavior of stunting prevention is influenced by prior related behavior that is supplementary feeding for pregnant women, overcoming iron and folic acid deficiency, providing worm medicine, providing complete immunization and preventing and treating diarrhea.